Six‐year analysis of compliance to weekly concurrent chemoradiotherapy in head and neck carcinomas. (11th February 2016) - Sharma, A.; Jagadesan, P.; Chaudhari, P.; Das, S.; Bhaskar, S.; Thakar, A.; Sharma, A.; Mohanti, B.K.
Abstract : Objectives: To evaluate treatment compliance to weekly concurrent chemoradiotherapy (CRT) in head and neck squamous cell carcinoma (HNSCC). Study design: Retrospective analysis. Setting: Tertiary care hospital. Main outcome measures: Overall treatment time (OTT), acute radiation morbidity and treatment completion rate without prolongation of overall treatment time of more than 2 days. Results: Three hundred and seventy‐eight head and neck carcinoma patients treated with radical CRT with 70 Gy/35 fractions of radiotherapy with weekly cisplatin 40 mg/m 2 were included in the study. Median age was 52 years (range 22–77 years), oropharynx was most commonly (54%) involved site, and 55% were in stage IV disease. Majority (86%) of patients were able to complete cancer‐directed therapy, median OTT was 52 days (46–140 days). Nineteen per cent of patients completed treatment without prolongation of OTT beyond 2 days and 68% of patients there completed treatment prolongation of OTT beyond 7 days. Nearly, sixty‐six of the patients experienced grade II or higher acute radiation morbidities. Conclusions: Delivery of weekly low‐dose concurrent CRT is safe and feasible. Two‐thirds of the patients experienced treatment prolongation of more than 2 days and 14% could not complete treatment. Results within in the study suggest to a greater need to lay emphasis on continuity of a course of radical CRT for HNSCC.